The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.12.20.21268136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The expansion and severity of chronic MS lesions follows a periventricular gradient

Abstract: Background and Objectives: Expansion of chronic lesions in MS patients and recently described CSF-related gradient of tissue damage are linked to microglial activation. The aim of the current study was to investigate whether lesion expansion is associated with proximity to ventricular CSF spaces. Methods: Pre- and post-gadolinium 3D-T1, 3D FLAIR and diffusion tensor images were acquired from 36 RRMS patients. Lesional activity was analysed between baseline and 48 months at different distances from the CSF usin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…Thus, for instance, it is feasible that soluble cytotoxic factors and/or inflammatory mediators produced by long-standing intrathecal inflammation (including choroid plexus, but also meningeal infiltrates and interstitial fluid 9 ) could diffuse from CSF into the periventricular white matter, forming /sustaining a permanent inflammatory environment in and around the ventricles, thereby driving slow-burning inflammation at the rim of chronic periventricular lesions. [39][40][41] This concept is supported by the recently described periventricular gradient of chronic lesion expansion, which demonstrated a decrease in a rate of chronic lesion enlargement as distance from the CSF (and plexus) increases 5 ; and by the observation reported in this study that the association between baseline plexus volume and lesion expansion is stronger in close proximity to the CSF. Notably, the periventricular gradient of lesion expansion is strikingly similar to the pattern of microstructural damage in the white matter described near the ventricles and in the most external cortical layers (i.e.…”
Section: Figure 6 Analysis Of Association Between Plexus Volume and C...supporting
confidence: 77%
See 1 more Smart Citation
“…Thus, for instance, it is feasible that soluble cytotoxic factors and/or inflammatory mediators produced by long-standing intrathecal inflammation (including choroid plexus, but also meningeal infiltrates and interstitial fluid 9 ) could diffuse from CSF into the periventricular white matter, forming /sustaining a permanent inflammatory environment in and around the ventricles, thereby driving slow-burning inflammation at the rim of chronic periventricular lesions. [39][40][41] This concept is supported by the recently described periventricular gradient of chronic lesion expansion, which demonstrated a decrease in a rate of chronic lesion enlargement as distance from the CSF (and plexus) increases 5 ; and by the observation reported in this study that the association between baseline plexus volume and lesion expansion is stronger in close proximity to the CSF. Notably, the periventricular gradient of lesion expansion is strikingly similar to the pattern of microstructural damage in the white matter described near the ventricles and in the most external cortical layers (i.e.…”
Section: Figure 6 Analysis Of Association Between Plexus Volume and C...supporting
confidence: 77%
“…[1][2][3][4] We recently demonstrated that lesion expansion is most noticeable in close proximity to ventricles, suggesting a link between slow burning inflammation and cerebrospinal fluid (CSF). 5 It is well established that the choroid plexus, located within the ventricular system of the central nervous system (CNS), plays an important role in the implementation of the immune response within the CNS. 6 The plexus is essential for the production of CSF, 7 but also responsible for regulating entry of immune cells and specific molecules to the brain parenchyma, providing a gateway for antigen trafficking between the CSF and the vascular circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for instance, it is feasible that soluble cytotoxic factors and/or inflammatory mediators produced by longstanding intrathecal inflammation (including choroid plexus, but also meningeal infiltrates and interstitial fluid 9 ) could diffuse from CSF into the periventricular white matter, forming /sustaining a permanent inflammatory environment in and around the ventricles, thereby driving slow-burning inflammation at the rim of chronic periventricular lesions. 37 38 39 This concept is supported by the recently described periventricular gradient of chronic lesion expansion, which demonstrated a decrease in a rate of chronic lesion enlargement as distance from the CSF (and plexus) increases 5 ; and by the observation reported in this study that the association between baseline plexus volume and lesion expansion is stronger in close proximity to the CSF. Notably, the periventricular gradient of lesion expansion is strikingly similar to the pattern of microstructural damage in the white matter described near the ventricles and in the most external cortical layers (i.e.…”
Section: Plexus Volume Correlates With Subsequent Expansion Of Chroni...supporting
confidence: 56%
“…1,2,3,4 We recently demonstrated that lesion expansion is most noticeable in close proximity to ventricles, suggesting a link between slow burning inflammation and cerebrospinal fluid (CSF). 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation